THE ORIENTAL SOLUTION OF THE PROBLEM OF DEATH AND LIFE IN PHILOSOPHY - Asliddin Ruziyev (Western European Studies, 2024)
Usually, many definitions of life do not indicate anything about its specific meaning. That is why the understanding of life is formed based on the characteristics of its carrier (owner) (for example, protein characteristics). It is also worth saying that in many cases the meaning of life is confused with the purpose of living. However, it is impossible to specify them, because the meaning of life is a very comprehensive concept of purpose, it includes dozens, if not hundreds of purposes, or rather, it consists of a certain system of purposes. Therefore, if someone's noble goal is not fulfilled, his life cannot be called "meaningless".
Keywords: death; survival; euthanasia